Spatial Changes in the Atrial Fibrillation Wave-Dynamics After Using Antiarrhythmic Drugs: A Computational Modeling Study - Hwang, Inseok; Jin, Ze; Park, Je-Wook; Kwon, Oh-Seok; Lim, Byounghyun; Lee, Jisu; Yu, Hee-Tae; Kim, Tae-Hoon; Joung, Boyoung; Pak, Hui-Nam (Frontiers in Physiology, 2021)
Background We previously reported that a computational modeling-guided anti-arrhythmic drug (AAD) test was feasible for evaluating multiple AADs in patients with atrial fibrillation (AF). We explored the anti-AF mechanisms of AADs and spatial change in the AF wave-dynamics by a realistic computational model. Methods We used realistic computational modeling of 25 AF patients (68% male, 59.8±9.8 years old, 32.0% paroxysmal AF) reflecting the anatomy, histology, and electrophysiology of the left atrium (LA) to characterize the effects of 5 AADs (amiodarone, sotalol, dronedarone, flecainide, and propafenone). We evaluated the spatial change in the AF wave-dynamics by measuring the mean dominant frequency (DF) and its coefficient of variation (DF-COV) in 10 segments of the LA. The mean DF and DF-COV were compared according to the pulmonary vein (PV) vs. extra-PV, maximal slope of the restitution curves (Smax), and defragmentation of AF. Results The mean DF decreased after the administration of AADs in the dose dependent manner (p<0.001). Under AADs, the DF was significantly lower (p<0.001) and COV-DF higher (p=0.003) in the PV than extra-PV region. The mean DF was significantly lower at a high Smax (Over 1.4) than a lower Smax condition under AADs. During the episodes of AF defragmentation, the mean DF was lower (p<0.001), but the COV-DF was higher (p<0.001) than that in those without defragmentation. Conclusions The DF reduction with AADs is predominant in the PVs and during a high Smax condition and causes AF termination or defragmentation during a lower DF and spatially unstable (higher DF-COV) condition.